2021
DOI: 10.1017/s1368980021003074
|View full text |Cite
|
Sign up to set email alerts
|

The association between low-carbohydrate diet score and metabolic syndrome among Iranian adults

Abstract: Objective: Assessing relationship between low carbohydrate diet (LCD) score and metabolic syndrome (Mets) in Iranian adults. Design: Cross-sectional study Setting: Yazd Health Study and Taghzieh Mardom-e-Yazd study. Participants: Data of 2074 participants were used. Dietary intakes were assessed by a validated semi-quantitative food frequency questionnaire. LCD score was calculated for each person by summing up the assigned scores to deciles of energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Also, the prevalence of MetS reduced by adherence to LCD score. Similar to our study, in the study by Sangesefidi ZS et al (Sangsefidi, Lorzadeh, et al, 2021), LCD score was associated with lower odds of metabolic syndrome and higher HDL concentrations. Also, Ha K et al , reported that LCD diet did not increase the risk of metabolic syndrome among Korean adults and reduced the risk of low HDL-cholesterol values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the prevalence of MetS reduced by adherence to LCD score. Similar to our study, in the study by Sangesefidi ZS et al (Sangsefidi, Lorzadeh, et al, 2021), LCD score was associated with lower odds of metabolic syndrome and higher HDL concentrations. Also, Ha K et al , reported that LCD diet did not increase the risk of metabolic syndrome among Korean adults and reduced the risk of low HDL-cholesterol values.…”
Section: Discussionsupporting
confidence: 92%
“…They also reported reduced plasma glucose, insulin, and HOMA‐IR, although we did not find any statistically significant difference in serum glucose or insulin level of highest versus lowest LCD categories, but, we found a significantly lower prevalence of MetS in those with highest adherence to LCD score. Similarly, numerous studies reported lower chance of MetS with higher adherence to low carbohydrate diet or with dietary carbohydrate restriction (Ha, Joung, & Song, 2018; Hyde et al, 2019; Kim et al, 2008; Sangsefidi, Lorzadeh, et al, 2021; Volek et al, 2008). In a nationwide cohort study by Li Q et al (Li et al, 2021), there was a U ‐shaped association between the percentage of carbohydrate intake (mean, 56.7%; SD, 10.7) and new‐onset hypertension ( p < 0.001), with the lowest risk observed at 50%–55% carbohydrate intake.…”
Section: Discussionmentioning
confidence: 94%
“…In the recent years, a low-carbohydrate-diet (LCD) score characterized by a diet with lower intake of carbohydrates and higher intakes of proteins and fats has been proposed [ 10 ]. LCD score has received widespread attention as a viable option for the treatment of losing weight and preventing obesity [ 11 , 12 ]. Previous studies have showed that LCD score was linked to many aspects of health, such as diabetes mellitus, coronary artery calcium progression, psychological disorders, and so on [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have showed that LCD score was linked to many aspects of health, such as diabetes mellitus, coronary artery calcium progression, psychological disorders, and so on [ 10 , 13 , 14 ]. Sangsefidi, et al reported that LCD score might be associated with lower chance of metabolic syndrome in Iranian adults based on a cross-sectional study [ 11 ]. However, to the best of our knowledge, few studies have explored the associations of LCD score and cognitive performance in the older adults so far.…”
Section: Introductionmentioning
confidence: 99%
“…Halton et al also created animal-based and plant-based LCD scores. Few studies have examined the relationship between the LCD score and cardiometabolic risk factors in adults, including blood lipid (21)(22)(23)(24)(25)(26)(27)(28) , fasting blood glucose (FBG) (21)(22)(23)(24)(25) , blood pressure (21,22,24,25,28) and uric acid (23) . There are several problems with these studies.…”
mentioning
confidence: 99%